PROBLEMS OF LONG-TERM CULTURAL RESISTANCE: THE CASE OF THE MEXICAN ZAPATISTAS - Kalpokas, Ignas (Politologija, 2015)
The Zapatista National Liberation Army first came to prominence on 1 January 1994 when they attacked several cities in the southern Mexican state of Chiapas in protest against the NAFTA agreement. Though having been quickly defeated by the Mexican Army, the movement was able to reorganize and reinvent itself, moving from armed struggle to socio-cultural resistance, and embracing the new opportunities, provided by the development of communications, thus outlining the path that was to be taken by other movements. However, the activity and popularity of the movement declined significantly, presumably due to its inability to sustain the momentum in the long-run. The article is aimed at analyzing long-term challenges faced by the Zapatistas as a paradigmatic case for other movements seeking radical political change by non-military means. These include the ideological, organizational and communicative plains. First of all, the openness of the Zapatista worldviews has had a paradoxical effect. It proved to be highly useful in the short-term, when many groups and individuals were attracted by the Zapatistas’ inclination to search for solutions rather than give final answers, by their pluralism and refutation of any hierarchy in power and knowledge. This, however, appeared as a self-defeating strategy when the Zapatistas had the possibility of constructing a nationwide reform movement and to propose a program for political change. This should be seen as a decisive moment, when the Zapatistas had to either betray their principle to ‘lead by obeying’ and to take initiative, or to risk losing the momentum, which was precisely what happened. The Zapatistas also failed to achieve substantive improvements in economic and social conditions of their communities. Although many Zapatista sympathisers were ready to accept hardship in the short run, later deep rifts and conflicts, especially over outside help, started to appear, with entire villages leaving the Zapatista front and siding with the government. The fact that the Zapatistas failed to create a viable practical alternative and to attract people even in their home region both diminished their credibility and led to an internal weakening of the movement. Finally, even though the Zapatistas were (and often still are) heralded for their innovative use of the Internet, this argument should also be reconsidered. While the movement has undoubtedly been successful in rallying support and spreading its message, the current situation appears to be less promising. Whereas the Zapatistas entered the Internet with no significant competition, the current surge and proliferation of information online as well as the loss of ‘freshness’ raises the costs of being heard significantly; furthermore, the bonds formed online tend to be fleeting and inconsistent, it appeared to be much more difficult to form stable supporters’ networks. All this raises significant doubts over the Zapatistas’ ability to remain effective in the long-term, something other radical movements should also take into account.